PENGARUH LABEL HALAL, BRAND IMAGE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of halal labels, brand image, and price on cosmetic purchasing decisions of STAINU Pacitan students. This study used quantitative research. The population in this study were all students at STAINU Pacitan, totaling 151 people. The sampling technique used was proportional random sampling. In this study, the number of samples was determined using the Slovin formula so that a sample size of 110 respondents was obtained. The results of the partial test (t-test) of the influence of variables X1, X2, and X3 on Y showed that the independent variables in this research model had a significance value of less than 0. 05, so that they partially had a significant effect on Y. The coefficients of all independent variables showed a positive effect. The results of the Simultaneous Test (F Test) were a significance value of 0. 000 <0. 05. Based on the Adjusted R-Square value, the independent variables in the model were able to explain 64. 4% of the variation in Y.